CARICOM environment in figures 2002 (CCS GeorgetownGY, 2003)
Provides an overview of the state of the environment in the CARICOM region through a presentation of the major issues, with supporting data in tables, charts and accompanying comments on the data.
Additional copy located in the Office of the Secretary-General